Tunable Dry Adhesion of Soft Hollow Pillars through Sidewall Buckling under Low Pressure. (22nd November 2022) - Wan, Guangchao; Tang, Yanbing; Turner, Kevin T.; Zhang, Teng; Shan, Wanliang
Abstract: Controlling adhesion on demand is essential for many manufacturing and assembly processes such as microtransfer printing. Among various strategies, pneumatics‐controlled switchable adhesion is efficient and robust but currently still suffers from challenges in miniaturization and high energy cost. In this paper,  a novel way to achieve tunable adhesion using low pressure by inducing sidewall buckling in soft hollow pillars (SHPs) is introduced. It is shown that the dry adhesion of these SHPs can be changed by more than two orders of magnitude (up to 151×) using low activating pressure (≈−10 or ≈20 kPa). Large enough negative pressure triggers sidewall buckling while positive pressure induces sidewall bulging, both of which can significantly change stress distribution at the bottom surface to facilitate crack initiation and reduce adhesion therein. It is shown that a single SHP can be activated by a micropump to manipulate various lightweight objects with different curvatures and surface textures. Here, it is also demonstrated that an array of SHPs can realize selective pick‐and‐place of an array of objects. These demonstrations illustrate the robustness, simplicity, and versatility of these SHPs with highly tunable dry adhesion. Abstract : A novel approach to tunable dry adhesion using soft hollow pillars (SHPs) under low pressure is introduced. Both negative and positive pressure can initially increase and then sharply decrease dry adhesion of a SHP when buckling/bulging of its sidewall alters stress distribution on its bottom contact surface. Dry adhesion changes of ≈100× are demonstrated using ≈±10 kPa.